The PENGEMBANGAN TOOL KIT PENINGKATAN KAPASITAS KEUANGAN KELUARGA CERMAT (TOOL KIT PK3C) BAGI PEREMPUAN DARI KELUARGA MISKIN DI KECAMATAN COBLONG KOTA BANDUNG - Hanifah Syahroeddin; Ellya Susilowati; Lina Favourita Setiaputri (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
Women from poor families have the potential to make poor financial decisions that exacerbate their poverty. The COVID-19 pandemic has driven the acceleration of digitalization and the demand for good financial literacy from poor families. Strengthening the role of women not only as targets but also agents of change in financial literacy can increase financial inclusion. This research objective is to develops a Tool Kit that can be used practically by women from poor families to conduct community-based learning independently. This Tool Kit design is called the Careful Family Financial Capacity building Tool Kit (PK3C Tool Kit). This study used a qualitative approach with the Participatory Action Research method. Data were collected using documentation studies, interviews, focused group discussions, and observations. The research participants were 15 women from poor families. Data analysis used the Miles and Huberman model. The findings of this study highlight the interaction of women from poor families in interacting with each other to learn financial literacy. Vicarious learning through the storytelling of financial experiences is considered to help women become financially literate. The learning scheme generated from the PK3C Tool Kit is a cycle consisting of a storytelling process, triggering discussion, reflection on experience, and discursive transformation related to new financial competencies.